Nitrogen availability mediates long-term warming effects on deep-soil dissolved organic matter concentration and composition in cropland - Xinhui Liu; Tim J. Clough; Dan Yuan; Jiao Yuan; Lin Ma; Chunsheng Hu; Wenxu Dong; Ping Wu; Shuping Qin; Oene Oenema (Agriculture, Ecosystems & Environment, 2026)

A membrane-anchored nanoscale zero-valent iron bio-interface enhances interspecies electron transfer in anaerobic membrane bioreactors - Mingchao Zhu; Huilai Zhang; Lin Zhang; Shuping Li; Shouwen Chen; Zhaoxia Hu; Jingwei Wang; Na Li; Yongze Lu (Bioresource Technology, 2026)

CRISPR/Cas12a and CHA-based SERS platform for ultrasensitive nucleic acid detection - Huimin Wang; Chengxin Bao; Lin Liu; Feiwu Li; Yuxuan He; Xiangguo Liu; Yuejia Yin; Shuping Xu (Analytica Chimica Acta, 2026)

A photothermal catalytic system based on phase change energy storage COF gel composites for solar-driven water-H2O2-electricity co-production - Shuping Jia; Weixiong Dong; Hongrui Jiang; Hongmei Li; Zhiqing Lin; Jun He (Chemical Engineering Journal, 2026)

Disrupting the lepidolite structure via low-temperature (NH4)2SO4 and Na2SO4 roasting: Achieving efficient co-extraction of lithium, rubidium, and cesium from lepidolite - Shuping Cheng; Zhipeng Rao; Jiezhong Zou; Junfeng Zhang; Guobiao Li; Huiquan Li; Ting Lai; Wanhai Xiao; Yong Lin; Tinggang Li; Dong Wang (Journal of Environmental Chemical Engineering, 2026)

An explainable machine learning model for accurate estimation of residual phthalate esters in Chinese agricultural soils - Weiwei Wang; Laigang Hu; Jialu Xu; Hongxia Zhu; Shuping Xing; Zhen Song; Yuchen Shen; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

Water stress influences aroma fate: The critical role of Zuoqing environmental relative humidity in oolong tea processing - Weiyi Kong; Qianlian Chen; Yuping Zhang; Jiake Zhao; Fangting Zhang; Shuping Ye; Junyang Wu; Jiao Feng; Hongzheng Lin; Zhilong Hao; Xiangxiang Huang (Food Research International, 2026)

Environmental airflow promotes sweet taste formation in white tea: Insights from metabolomic, transcriptomic and microstructure - Jiao Feng; Junyang Wu; Kailong Liu; Shuping Ye; Kexin Lin; Linling He; Xiangxiang Huang; Dongliang Qiu; Wei Wang; Zhilong Hao (Food Chemistry, 2026)

Revealing speciation transformation and stabilization mechanisms of associated trace hazardous beryllium and thallium during lithium extraction: Achieving targeted detoxification of lithium slag - Shuping Cheng; Yong Lin; Yanxi Zeng; Guobiao Li; Jiezhong Zou; Zhihan Zhang; Zhi Wang; Tao Qi; Huiquan Li; Wanhai Xiao; Tinggang Li; Dong Wang (Journal of Hazardous Materials, 2026)

Encoding intrinsic rare-earth dissolution selectivity into deep eutectic solvents via coordination-active functional group design - Zhihan Zhang; Guobiao Li; Zhi Wang; Wanhai Xiao; Yong Lin; Shuping Cheng; Rui Min; Jian Wu; Mingqing Liu; Dong Wang (Journal of Cleaner Production, 2026)

Quinone-loaded biochar amplifies soil N2O mitigation by enhancing electron transfer for N2O reduction - Jiao Yuan; Dan Yuan; Tim J. Clough; Xinhui Liu; Lin Ma; Chunsheng Hu; Shuping Qin (Soil Biology and Biochemistry, 2026)

Reduction mediated iodide antioxidation: “Chemical Preservation” of precursor solution facilitates construction of high efficiency and stable wide bandgap inverted perovskite solar cells - Chao Liu; Yingchen Li; Hongkun Cai; Boyan Li; Shuping Lin; Qi Sun; Dalong Zhong; Jifeng Liu; Qinwen Guo; Zhiwen Xu; Juan Li; Jian Ni; et al. (Chemical Engineering Journal, 2026)

Emerging tire additives and their quinone derivatives in marine species: Characteristics, sources, and health risks - Yiqing Xing; Shuping Tan; Shuaidan Chang; Xiaoqin Lin; Peixuan Li; Jiong Liu; Tao Zhou; Ji-Chang Zhou; Yanhao Zhang; Chunxue Yang (Journal of Hazardous Materials, 2026)

Hierarchical rGO/MXene aerogels assembled with SiC nanowires for excellent electromagnetic wave absorption and multifunctionality - Jiaqi Tan; Shuping Wen; Xiaoqian Lin; Liya Zheng; Zhilin Tian; Bin Li (Chemical Engineering Journal, 2025)

The role of endoplasmic reticulum stress in Atrazine-induced hepatic lipid accumulation - Honghao Qian; Shuping Ren; Haotang Zhao; Jingjing Shi; Zhili Ge; Jiaxin Zhang; Tianyou Wang; Xinyu Zhang; Huibin Jiang; Yuezhu Zhang; Lin Ye (Toxicology Letters, 2025)

Synergistic effect of hollow n-Al/H-MoO3 in the gas-phase reaction zone of solid propellant - Shuping Li; Cheng Dong; Xuan Qi; Shiyong Chen; Lixiao Shen; Yinning Zeng; Yan Li; Zhenxin Yi; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Overexpression of GPX4 in diabetic rat kidney alleviates renal injury induced by ferroptosis - Keping Wu; Enyi Zhu; Jiasi Chen; Qingyan Kuang; Jiawen Lin; Shuping Zhao; Xiaochang Xu; Shuping Li; Yuan Sui; Mingcheng Huang; Yimin Zhang (BioMetals, 2025)

From water migration to aroma development: Revealing the influence of environmental airflow on the aroma of white tea during withering - Jiao Feng; Shuping Ye; Jinyuan Wang; Junyang Wu; Jiake Zhao; Weisu Tian; Guanjun Pan; Bugui Yu; Dongliang Qiu; Hongzheng Lin; Zhilong Hao (Food Chemistry, 2025)

Robust titanium suboxide anodes doped by sintering enhance PFOS degradation in water - Yufei Sui; Xi Zhu; Lei Li; Yaye Wang; Gengyang Li; Shuping Dong; Yifei Wang; Hui Lin; Ke Li; Qingguo Huang (Chemosphere, 2025)

Another inner truth of shaking: Water migration and transformation-advanced physicochemical alterations in tea leaves - Zhilong Hao; Jinyuan Wang; Jiayun Zhuang; Xinyu Feng; Helin Lv; Jiao Feng; Shuping Ye; Weisu Tian; Guanjun Pan; Ping Chen; Hongzheng Lin; Qiang Chu (Food Chemistry, 2025)

Peroxymonosulfate-based electrochemical advanced oxidation for pollutant degradation: Roles of Co-phase regulation and electro-induced polarized particle electrodes - Yunlong Liu; Ran Hao; Zhenyu Shi; Wei Zhang; Can Jin; Liang Zhu; Chunmei Tang; Guifeng Liu; Shuping Huo; Lin Xu; Zhenwu Kong (Chemical Engineering Journal, 2024)

Signature and function of plasma exosome-derived circular RNAs in patients with hypertensive intracerebral hemorrhage - Kejie Chen; Xiaoyuan Cheng; Shanshan Yuan; Yang Sun; Junli Hao; Quandan Tan; Yapeng Lin; Shuping Li; Jie Yang (Molecular Genetics and Genomics, 2024)

Modifying functional groups of straw-based hydrogel provide soil N2O mitigation potential by complete denitrification - Weishuai Wang; Xuan Wang; Shuping Qin; Jiao Yuan; Jiafa Luo; Zhaohai Bai; Lin Ma (Chemical Engineering Journal, 2024)

Sex and age disparities in multi-metal mixture exposure and cognitive impairment in urban elderly individuals: The mediation effect and biological function of metabolites - Qingzhi Hou; Jiujing Lin; Xiangsheng Xue; Yuchen Zhang; Zhanhui Qiu; Haoran Zhang; Jia Li; Harry Wang; Shuping Zhang; Zhigang Yao; Xiaomei Li; Fei Wang; et al. (Science of The Total Environment, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Foliar N 2 O emissions constitute a significant source to atmosphere - Shuping Qin; Yaxing Pang; Huixian Hu; Ting Liu; Dan Yuan; Timothy Clough; Nicole Wrage‐Mönnig; Jiafa Luo; Shungui Zhou; Lin Ma; Chunsheng Hu; Oene Oenema (Global Change Biology, 2024)
Nitrous oxide (N 2 O) is a potent greenhouse gas and causes stratospheric ozone depletion. While the emissions of N 2 O from soil are widely recognized, recent research has shown that terrestrial plants may also emit N 2 O from their leaves under controlled laboratory conditions. However, it is unclear whether foliar N 2 O emissions are universal across varying plant taxa, what the global significance of foliar N 2 O emissions is, and how the foliage produces N 2 O in situ. Here we investigated the abilities of 25 common plant taxa, including trees, shrubs and herbs, to emit N 2 O under in situ conditions. Using 15 N isotopic labeling, we demonstrated that the foliage‐emitted N 2 O was predominantly derived from nitrate. Moreover, by selectively injecting biocide in conjunction with the isolating and back‐inoculating of endophytes, we demonstrated that the foliar N 2 O emissions were driven by endophytic bacteria. The seasonal N 2 O emission rates ranged from 3.2 to 9.2 ng N 2 O–N g −1 dried foliage h −1 . Extrapolating these emission rates to global foliar biomass and plant N uptake, we estimated global foliar N 2 O emission to be 1.21 and 1.01 Tg N 2 O–N year −1 , respectively. These estimates account for 6%–7% of the current global annual N 2 O emission of 17 Tg N 2 O–N year −1 , indicating that in situ foliar N 2 O emission is a universal process for terrestrial plants and contributes significantly to the global N 2 O inventory. This finding highlights the importance of measuring foliar N 2 O emissions in future studies to enable the accurate assigning of mechanisms and the development of effective mitigation.

Experimental study on exploration of optimum extinguishing agent for 243 Ah lithium iron phosphate battery fires - Xiangdong Meng; Lihua Jiang; Qiangling Duan; Shuping Wang; Peiyu Duan; Zesen Wei; Lin Zhang; Zhuangzhuang Jia; Kaiqiang Jin; Qingsong Wang (Process Safety and Environmental Protection, 2023)

Enhanced degradation of microplastics during sludge composting via microbially-driven Fenton reaction - Ruizhi Xing; Hanyue Sun; Xian Du; Hao Lin; Shuping Qin; Zhi Chen; Shungui Zhou (Journal of Hazardous Materials, 2023)

The Novel Fluorescent Probe Toward Yttrium(III) and its Bioimaging - Yuxin Qin; Qian Meng; Junxiong Yao; Mengyu Chen; Yajie Dong; Dashuo Chen; Shuping He; Cuibing Bai; Lin Zhang; Biao Wei; Hui Miao; Changqing Qu; et al. (Journal of Fluorescence, 2023)

Oxygen activity excited thiophene-diketopyrrolopyrrole-based organic molecules as anode for lithium-ion batteries with enhanced interfacial storage capacity and long cycling capability - Zichen Xu; Shengxian Hou; Zhiqiang Zhang; Jing Yang; Yingzhi Cheng; Pengfei Zhou; Hongtao Lin; Shuhai Chen; Jin Zhou; Shuping Zhuo (Chemical Engineering Journal, 2023)

Long term toxicities following developmental exposure to perfluorooctanoic acid: Roles of peroxisome proliferation activated receptor alpha - Hao Ni; Junhua Yuan; Jing Ji; Yajie Guo; Shuping Zhong; Yongfeng Lin; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2023)

Identification and Functional Characterization of a Novel Δ12 Fatty Acid Desaturase Gene from Haematococcus pluvialis - Lin Zhang; Wenbi Chen; Shuping Yang; Yuanbo Zhang; Jilin Xu; Dongjie Yang; Zuyao Wu; Tong Liu; Jiayi Cao (Journal of Ocean University of China, 2020)

Application of exogenous salicylic acid on improving high temperature resistance of Nannochloropsis oceanica - Lin Zhang; Shuping Yang; Jilin Xu; Tong Liu; Dongjie Yang; Zuyao Wu; Mengjie Shao (Aquaculture International, 2020)

Identification of PP2A and S6 Kinase as Modifiers of Leucine-Rich Repeat Kinase-Induced Neurotoxicity - Joan Poh Ling Sim; Wang Ziyin; Adeline Henry Basil; Shuping Lin; Zhongcan Chen; Chengwu Zhang; Li Zeng; Yu Cai; Kah-Leong Lim (NeuroMolecular Medicine, 2020)
Mutations in LRRK2 are currently recognized as the most common monogenetic cause of Parkinsonism. The elevation of kinase activity of LRRK2 that frequently accompanies its mutations is widely thought to contribute to its toxicity. Accordingly, many groups have developed LRRK2-specific kinase inhibitors as a potential therapeutic strategy. Given that protein phosphorylation is a reversible event, we sought to elucidate the phosphatase(s) that can reverse LRRK2-mediated phosphorylation, with the view that targeting this phosphatase(s) may similarly be beneficial. Using an unbiased RNAi phosphatase screen conducted in a Drosophila LRRK2 model, we identified PP2A as a genetic modulator of LRRK2-induced neurotoxicity. Further, we also identified ribosomal S6 kinase (S6K), a target of PP2A, as a novel regulator of LRRK2 function. Finally, we showed that modulation of PP2A or S6K activities ameliorates LRRK2-associated disease phenotype in Drosophila .

Molecular analyses of bacterioplankton communities with highly abundant Vibrio clades: a case study in Bohai Sea coastal waters - Shuping Wang; Yuan Zhang; Jia He; Xiaobo Jia; Jianing Lin; Meng Li; Qinglin Wang (Journal of Oceanology and Limnology, 2019)

QTL analysis of nodule traits and the identification of loci interacting with the type III secretion system in soybean - Jingyi Zhu; Jinhui Wang; Qingying Li; Jieqi Wang; Yang Liu; Jianyi Li; Lin Chen; Yan Shi; Shuping Li; Yongqian Zhang; Xueying Liu; Chao Ma; et al. (Molecular Genetics and Genomics, 2019)

Nodulation and Genomic Capacity of a Novel High-Latitude Bradyrhizobium japonicum HLNEAU001 - Yan Shi; Jianyi Li; Jinhui Wang; Rongsheng Zhu; Shuping Li; Qingying Li; Lin Chen; Jingyi Zhu; Jianan Zou; Jieqi Wang; Huilin Chang; Chao Ma; et al. (Journal of Soil Science and Plant Nutrition, 2019)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)